Histidine decarboxylase (HDC)-expressing granulocytic myeloid cells induce and recruit Foxp3+ regulatory T cells in murine colon cancer. (4th March 2017) - Chen, Xiaowei; Takemoto, Yoshihiro; Deng, Huan; Middelhoff, Moritz; Friedman, Richard A.; Chu, Timothy H.; Churchill, Michael J.; Ma, Yan; Nagar, Karan K.; Tailor, Yagnesh H.; Mukherjee, Siddhartha; Wang, Timothy C.
ABSTRACT: The colorectal tumor microenvironment contains a diverse population of myeloid cells that are recruited and converted to immunosuppressive cells, thus facilitating tumor escape from immunoediting. We have identified a genetically and functionally distinct subset of dynamic bone marrow myeloid cells that are characterized by histidine decarboxylase (HDC) expression. Lineage tracing in Hdc-CreERT2;R26-LSL-tdTomato mice revealed that in homeostasis, there is a strong bias by HDC + myeloid cells toward the CD11b + Ly6G hi granulocytic lineage, which was accelerated during azoxymethane/dextran sodium sulfate (AOM/DSS)-induced colonic carcinogenesis. More importantly, HDC + myeloid cells strongly promoted colonic tumorigenesis, and colon tumor progression was profoundly suppressed by diphtheria toxin A (DTA)-mediated depletion of HDC + granulocytic myeloid cells. In addition, tumor infiltration by Foxp3 + regulatory T cells (Tregs) was markedly impaired following HDC + myeloid cell depletion. We identified an HDC + myeloid-derived Cxcl13/Cxcr5 axis that mediated Foxp3 expression and Treg proliferation. Ablation of HDC + myeloid cells or disruption of the Cxcl13/Cxcr5 axis by gene knockdown impaired the production and recruitment of Tregs. Cxcl13 induction of Foxp3 expression in Tregs during tumorigenesis was associated with Stat3 phosphorylation. Overall, HDC + granulocytic myeloid cells affect CD8 + T cells directly and indirectly through the modulation of Tregs and thus appear to play key roles in suppressing tumoricidal immunity.